Lead-free ceramic with fast and efficient photostrictive response and preparation method thereof
By doping Tb, Bi and Li elements in K0.5Na0.5NbO3-based ceramics and optimizing the sintering process, the existing photostrictive ceramic materials have problems such as lead pollution, low light transmission and slow response, and the rapid and efficient photostrictive response and ultrasonic generation of lead-free ceramic materials are achieved, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202411116885.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-08-14
AI Technical Summary
Existing photostrictive ceramic materials have problems such as lead pollution, low light transmission and slow response, which is difficult to meet the demand for high-efficiency photostrictive materials in industrial applications.
By doping Tb, Bi and Li elements in K0.5Na0.5NbO3-based ceramics and optimizing the sintering process, the domain size is reduced to the nanoscale, and local piezoelectric response and light transmission are improved.
It realizes the rapid and efficient photostriction response of lead-free ceramic materials, can generate significant strain and ultrasonic waves, and the materials are environmentally friendly and suitable for industrial production.
Smart Images

Figure CN118851761B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular to a lead-free ceramic with fast and efficient photostrictive response and a preparation method thereof. Background Art
[0002] In the field of light-to-mechanical energy conversion, efficiently converting light energy into mechanical energy is a promising method involving applications such as wireless driving, imaging, sensing, and quantum information processing. However, current technologies have not been able to meet the wide range of industrial applications in terms of energy conversion efficiency and mechanical strain generation time, such as ultrasonic detection and photoacoustic imaging.
[0003] At present, the technologies for converting light energy into mechanical energy mainly include three types of technologies: photoinduced thermoelastic expansion, molecular structure transformation, and ferroelectric photostriction. Among them, the efficiency of photoinduced thermoelastic expansion is relatively low and requires short and intense laser pulses, which increases the cost of equipment and the complexity of operation. Although the molecular structure transformation can produce significant strain, its kinetic process is slow and usually irreversible, which limits its application in the field of high frequency and precise mechanical control. Ferroelectric photostriction is based on the synergistic effect of volume photovoltaic effect (BPVE) and inverse piezoelectric effect. The internal electric field is formed in the direction of spontaneous polarization through the external light field, thereby realizing the mechanical strain controlled by light. This mechanism provides a cost-effective and reversible method to accurately generate mechanical strain through light. However, its effect is mainly limited by the slow accumulation of photovoltage (from tens of milliseconds to seconds) and the interaction between light and lattice at the surface level (the effective thickness is only tens of nanometers), which limits its potential in bulk ferroelectrics that can generate stronger sound pressure. Therefore, developing bulk ferroelectric materials that can participate in more lattice sites and respond to light faster and more efficiently will greatly improve the conversion efficiency of light to acoustic energy and promote the application of photostrictive materials in advanced acousto-optic technologies.
[0004] Photostrictive ceramics are such a type of bulk functional material with photostrictive effect, but traditional photostrictive ceramics usually contain lead, such as Pb(Zr,Ti)O3(PZT), which is harmful to the environment. In addition, traditional photostrictive ceramics also have problems such as low light transmittance and slow photostrictive response. Summary of the invention
[0005] The purpose of the present invention is to provide a lead-free ceramic with fast and efficient photostrictive response and a preparation method thereof, in which potassium sodium niobate K 0.5 Na 0.5By cation doping and process control in NbO3-based ceramics, the electric domain size can be reduced from the micron level to the nanometer level, and its local piezoelectric response can be improved. After optimizing the sintering process, the best light transmittance can be obtained, thereby improving the efficiency of photogenerated carriers migrating to the domain wall to shield the depolarization field, thereby effectively improving the photostrictive performance.
[0006] To achieve the above object, the present invention provides a lead-free ceramic having a fast and efficient photostrictive response, comprising K 0.5 Na 0.5 NbO3-based ceramics and doping elements, the doping elements are Tb, Bi and Li, and the chemical formula of lead-free ceramics is:
[0007] [(K 0.5 Na 0.5 ) 1-z Li z ](Nb 1-y Bi y )O3-xTb;
[0008] Wherein, x, y, z represent the doping amount, x, y, z = 0 to 0.1.
[0009] It should be noted that the “-” in the general formula represents a uniform compound formed by doping multiple components.
[0010] In the present invention, by changing x, y, z, K can be regulated. 0.5 Na 0.5 Properties of NbO3-based ceramics.
[0011] The photostrictive lead-free ceramic of the present invention is provided by using Tb, Bi, Li elements to react with K 0.5 Na 0.5 The NbO3 ceramic matrix is modified by cation doping and sintering to obtain a photostrictive ceramic structure with "orthorhombic-tetragonal-cubic" multiphase coexistence at room temperature and high transmittance under visible light. This structure can significantly reduce the size of the ferroelectric domain structure to the nanometer level, optimize the local piezoelectric properties, and thus obtain a fast and efficient photostrictive response.
[0012] The method for preparing the lead-free ceramic with fast and efficient photostrictive response comprises the following steps:
[0013] S101, selecting potassium carbonate, sodium carbonate, niobium pentoxide, bismuth oxide, lithium carbonate, and terbium oxide as raw materials according to molar percentage, and using anhydrous ethanol as a ball milling medium, rolling ball milling to obtain a uniform powder;
[0014] S102, drying the powder obtained in S101 to obtain a uniformly mixed powder;
[0015] S103, pre-calcining the powder obtained in S102 at 700-900° C. for 2-9 hours to obtain dry powder;
[0016] S104, adding a polyvinyl alcohol aqueous solution to the dry powder obtained in S103, and sequentially performing granulation, pressing and debinding to obtain a ceramic body;
[0017] S105, sintering the ceramic body obtained in S104 at 1000-1200° C. for 5-20 hours to obtain a photostrictive lead-free ceramic body;
[0018] S106. Cut the lead-free ceramic body obtained in S105 into a ceramic cantilever beam with a length×width×height of 3.00 mm×0.25 mm×0.50 mm using a precision cutting machine.
[0019] Preferably, the ball milling jar used in the ball milling in S101 is a nylon jar, and the grinding balls used are zirconium balls.
[0020] Preferably, during the pre-firing in S103, the powder is placed in a corundum crucible, and the corundum crucible is pre-firing at 700 to 900° C. for 2 to 9 hours.
[0021] Preferably, the pressing in S104 is as follows: placing the dry powder in a mold having a cavity, and pressing the dry powder into a sheet using a hand-cranked tablet press or an electric tablet press.
[0022] Preferably, the pressure of the electric tablet press is 5 to 10 MPa.
[0023] Preferably, the mass percentage of the polyvinyl alcohol aqueous solution in S104 is 3wt% to 8wt%.
[0024] Beneficial effects of the present invention:
[0025] (1) The present invention provides a lead-free ceramic with fast and efficient photostrictive response, which is co-doped with Tb, Bi, and Li elements. 0.5 Na 0.5 The NbO3 ceramic matrix is sintered to obtain an electronic ceramic structure with "orthorhombic-tetragonal-cubic" multiphase coexistence at room temperature. On this basis, the light transmittance of the ceramic is further regulated by optimizing the process parameters, so that the electric domain size of the prepared photostrictive ceramic material is reduced to the nanoscale, and the local piezoelectric performance is enhanced. Finally, a fast and efficient photostrictive response is obtained, which can be used to generate ultrasound.
[0026] (2) The lead-free ceramic material with the best photostrictive response prepared by the present invention has a maximum displacement of 202 nanometers at its resonant frequency and an effective strain of 1.12×10 -5 , the strain rate is 6.413×10 -1 s -1The photostrictive ceramic material does not contain lead elements, is an environmentally friendly material, conforms to the sustainable development strategy of the current international community, and has a very wide range of applications.
[0027] (4) The present invention provides a method for preparing a lead-free ceramic with a fast and efficient photostrictive response, which has a simple and stable process, is easy to operate, and is convenient for industrial production.
[0028] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic flow chart of a method for preparing a lead-free ceramic with photostrictive response according to the present invention;
[0030] Figure 2 is an X-ray diffraction pattern of the lead-free ceramic material of the photostrictive response of Examples 1-6 of the present invention;
[0031] Figure 3 is a test result diagram of the photoinduced strain generated by the lead-free ceramic material with photostrictive response provided by Example 4 of the present invention under light-driven conditions;
[0032] Figure 4 It is a comparison diagram of the photoinduced strain and photoinduced strain rate of the lead-free ceramic materials of the photostrictive response of Examples 1-6 of the present invention as a function of the composition;
[0033] Figure 5 This is a diagram of the electric domain structure of the lead-free ceramic material with photostrictive response in Examples 1, 3, 4, and 6 of the present invention, taken with a piezoelectric force microscope;
[0034] Figure 6 It is a deformation amount diagram corresponding to the micro-domain reversal of the lead-free ceramic material of the photostrictive response of Examples 1, 3, 4, and 6 of the present invention;
[0035] Figure 7 It is a phase diagram corresponding to the micro-domain reversal of the lead-free ceramic material of the photostrictive response of embodiments 1, 3, 4, and 6 of the present invention;
[0036] Figure 8 This is a test result diagram of the ceramic cantilever beam of Example 4 of the present invention used to generate ultrasonic waves. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with the accompanying drawings and embodiments. Unless otherwise defined, the technical terms or scientific terms used in the present invention should be the common meanings understood by people with ordinary skills in the field to which the present invention belongs. The above-mentioned features or features mentioned in the specific examples mentioned in the present invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0038] The present invention provides a lead-free ceramic having a fast and efficient photostrictive response, comprising K 0.5 Na 0.5 NbO3-based ceramics and doping elements, the doping elements are Tb, Bi and Li, and the chemical formula of lead-free ceramics is:
[0039] [(K 0.5 Na 0.5 ) 1-z Li z ](Nb 1-y Bi y )O3-xTb;
[0040] Wherein, x, y, z represent the doping amount, x, y, z = 0 to 0.1.
[0041] It should be noted that the “-” in the general formula represents a uniform compound formed by doping multiple components.
[0042] In the present invention, K can be regulated by changing x, y, and z. 0.5 Na 0.5 Properties of NbO3-based ceramics.
[0043] The photostrictive lead-free ceramic of the present invention is provided by using Tb, Bi, Li elements to react with K 0.5 Na 0.5 The NbO3 ceramic matrix is modified by cation doping and sintered to obtain a photostrictive ceramic structure with "orthogonal-tetragonal-cubic" multiphase coexistence at room temperature. This "orthogonal-tetragonal-cubic" multiphase coexistence structure reduces polarization anisotropy, can refine ferroelectric domains, reduce polarization barriers, and thus improve the efficiency of the micro-region bulk photovoltaic effect and micro-region piezoelectric performance of the lead-free ceramic material with photostrictive response of the present invention. On this basis, the sintering process is optimized to achieve an improvement in the transmittance of the lead-free ceramic under visible light, thereby allowing more excitation light to participate in the interaction with the lattice inside the ceramic, thereby improving the photostrictive performance of the ceramic.
[0044] It should be noted that in the lead-free ceramic material of the photostrictive response of the present invention, the atomic ratios of K element, Na element, Li element, Nb element, Bi element and O element need to be 0.5×(1-z), 0.5×(1-z), z, 1-y, y and 3 according to the electric charge balance. Otherwise, when the ratio changes, its phase structure will change, and a second phase will be generated, resulting in a decrease in its photostrictive performance. When the molar percentages of all the above components or atomic contents deviate greatly from the range of x, y, z=0 to 0.1, over-doping is likely to occur, forming a heterogeneous phase retained in the photostrictive ceramic structure of "orthorhombic-tetragonal-cubic" multi-phase coexistence, resulting in a decrease in its photostrictive performance.
[0045] The method for preparing the lead-free ceramic with fast and efficient photostrictive response comprises the following steps:
[0046] S101. According to molar percentage, select analytically pure sodium carbonate (Na2CO3), potassium carbonate (K2CO3), niobium pentoxide (Nb2O5), bismuth oxide (Bi2O3), lithium carbonate (Li2CO3), and terbium oxide (Tb2O3), and use anhydrous ethanol as a ball milling medium to obtain a uniform powder by rolling ball milling;
[0047] S102, drying the powder obtained in S101 to obtain a uniformly mixed powder;
[0048] S103, pre-calcining the powder obtained in S102 at 700-900° C. for 2-9 hours to obtain dry powder;
[0049] S104, adding a polyvinyl alcohol aqueous solution to the dry powder obtained in S103, and sequentially performing granulation, pressing and debinding to obtain a ceramic body;
[0050] S105, sintering the ceramic body obtained in S104 at 1000-1200° C. for 5-20 hours to obtain a photostrictive lead-free ceramic body;
[0051] S106. Cut the lead-free ceramic body obtained in S105 into a ceramic cantilever beam with a length×width×height of 3.00 mm×0.25 mm×0.50 mm using a precision cutting machine.
[0052] Preferably, the ball milling jar used in the ball milling in S101 is a nylon jar, and the grinding balls used are zirconium balls.
[0053] Preferably, during the pre-firing in S103, the powder is placed in a corundum crucible, and the corundum crucible is pre-firing at 700 to 900° C. for 2 to 9 hours.
[0054] Preferably, the pressing in S104 is as follows: placing the dry powder in a mold having a cavity, and pressing the dry powder into a sheet using a hand-cranked tablet press or an electric tablet press.
[0055] Preferably, the pressure of the electric tablet press is 5 to 10 MPa.
[0056] Preferably, the mass percentage of the polyvinyl alcohol aqueous solution in S104 is 3wt% to 8wt%.
[0057] If the mass percentage of the polyvinyl alcohol aqueous solution in the present invention is lower than 3wt%, the sample may not be formed and the photostrictive ceramic material may not be obtained. If the mass percentage of the polyvinyl alcohol aqueous solution is higher than 8wt%, the light transmittance of the sample may be reduced or holes may exist in the sample, resulting in the inability to obtain a dense photostrictive ceramic material.
[0058] More preferably, the mass percentage of the polyvinyl alcohol aqueous solution is 6wt%.
[0059] Example 1
[0060] Figure 1 The schematic diagram of the process of preparing the lead-free ceramic with photostrictive response of the present invention is shown in the figure. As shown in the figure, the present invention provides a lead-free ceramic with fast and efficient photostrictive response. In the general formula, x, y, and z are all 0. The chemical formula of the lead-free ceramic is: K 0.5 Na 0.5 NbO3.
[0061] The method for preparing the lead-free ceramic with fast and efficient photostrictive response comprises the following steps:
[0062] S101, select analytically pure Na2CO3, K2CO3, Nb2O5 as raw materials, accurately weigh each raw material according to molar percentage, use anhydrous ethanol as ball milling medium, use zirconium balls as grinding balls, roll the weighed raw materials in a nylon jar for 24 hours to obtain a uniform powder;
[0063] S102, drying the powder obtained in S101 to obtain a uniformly mixed powder;
[0064] S103, putting the powder obtained in S102 into a corundum crucible, and then pre-calcining the corundum crucible at 850° C. for 6 hours to obtain dry powder;
[0065] S104, adding 6 wt% polyvinyl alcohol aqueous solution to the dry powder obtained in S103 for granulation, and after granulation, using a mold with a diameter of 10 mm to press into small discs at a pressure of 10 MPa, with a diameter of 10 mm and a thickness of 1 mm, and then removing the glue to obtain a ceramic body.
[0066] S105, sintering the debinded ceramic body at 1100° C. for 5 hours to obtain a photostrictive lead-free ceramic body;
[0067] S106. Cut the lead-free ceramic body obtained in S105 into a ceramic cantilever beam with a length×width×height of 3.00 mm×0.25 mm×0.50 mm using a precision cutting machine.
[0068] The ceramic cantilever beam is fixedly clamped in a fixture of the prior art, a laser with rapidly modulated light intensity is used to excite the vibration of the ceramic cantilever beam, and a laser vibrometer is used to test the photostrictive performance.
[0069] Example 2
[0070] The present invention provides a lead-free ceramic with fast and efficient photostrictive response, wherein x=0, y=0.03, z=0.06, and the chemical formula of the lead-free ceramic is: (K 0.5 Na 0.5 ) 0.94 Li 0.06 (Nb 0.97 Bi 0.03 )O3.
[0071] The preparation method of the lead-free ceramic with fast and efficient photostrictive response is similar to the preparation method of Example 1, except that the molar percentage of the raw materials in S101 is weighed according to the chemical formula in this example, and the sintering condition in S105 is sintering at 1090° C. for 5 hours.
[0072] Example 3
[0073] The present invention provides a lead-free ceramic with fast and efficient photostrictive response, wherein x=0.01, y=0.03, z=0.06, and the chemical formula of the lead-free ceramic is: (K 0.5 Na 0.5 ) 0.94 Li 0.06 (Nb 0.97 Bi 0.03 )O3-0.01Tb.
[0074] The preparation method of the lead-free ceramic with fast and efficient photostrictive response is similar to the preparation method of Example 1, except that the molar percentage of the raw materials in S101 is weighed according to the chemical formula in this example, and the sintering condition in S105 is sintering at 1080° C. for 10 hours.
[0075] Example 4
[0076] The present invention provides a lead-free ceramic with fast and efficient photostrictive response, wherein x=0.02, y=0.03, z=0.06, and the chemical formula of the lead-free ceramic is: (K 0.5 Na 0.5 ) 0.94 Li 0.06 (Nb 0.97 Bi 0.03 )O3-0.02Tb.
[0077] The preparation method of the lead-free ceramic with fast and efficient photostrictive response is similar to the preparation method of Example 1, except that the molar percentage of the raw materials in S101 is weighed according to the chemical formula in this example, and the sintering condition in S105 is sintering at 1080° C. for 10 hours.
[0078] Example 5
[0079] The present invention provides a lead-free ceramic with fast and efficient photostrictive response, wherein x=0.03, y=0.03, z=0.06, and the chemical formula of the lead-free ceramic is: (K 0.5 Na 0.5 ) 0.94 Li 0.06 (Nb 0.97 Bi 0.03 )O3-0.03Tb.
[0080] The preparation method of the lead-free ceramic with fast and efficient photostrictive response is similar to the preparation method of Example 1, except that the molar percentage of the raw materials in S101 is weighed according to the chemical formula in this example, the pre-firing condition in S103 is pre-firing at 880° C. for 6 hours, and the sintering condition in S105 is sintering at 1080° C. for 10 hours.
[0081] Example 6
[0082] The present invention provides a lead-free ceramic with fast and efficient photostrictive response, wherein x=0.04, y=0.03, z=0.06, and the chemical formula of the lead-free ceramic is: (K 0.5 Na 0.5 ) 0.94 Li 0.06 (Nb 0.97 Bi 0.03 )O3-0.04Tb.
[0083] The preparation method of the lead-free ceramic with fast and efficient photostrictive response is similar to the preparation method of Example 1, except that the molar percentage of the raw materials in S101 is weighed according to the chemical formula in this example, the pre-firing condition in S103 is pre-firing at 880° C. for 6 hours, and the sintering condition in S105 is sintering at 1080° C. for 10 hours.
[0084] Performance Testing
[0085] Figure 2 is the X-ray diffraction pattern of the lead-free ceramic material of the photostrictive response of Examples 1-6 of the present invention, such as Figure 2As shown, there are 7 characteristic peaks between 20-70°, which are
[100] ,
[110] ,
[002] ,
[200] ,
[210] ,
[211] , and
[220] as the angle increases, indicating that the lead-free ceramic material is a perovskite ceramic. Split peaks appear near 45-46°, which are
[002] and
[200] peaks, respectively. The peak intensity ratio of the two deviates from 1:2 or 2:1, excluding pure T or O phase, indicating that the lead-free ceramic is a multi-phase coexistence structure; the peak shape of the XRD graph of the lead-free ceramic with x content in the range of 0.01≤x≤0.04 is basically consistent, indicating that the lead-free ceramic structure shown in Examples 1-6 is relatively stable and always multi-phase coexistence.
[0086] The photostriction test of the lead-free ceramic materials with photostrictive response in Examples 1-6 is carried out. The test principle is as follows: the laser controller controls the frequency of the input voltage, and the intensity of the laser generated in the laser generator can be modulated by the frequency-modulated voltage signal. The modulated laser is linearly focused through the lens module and irradiated on the upper or lower half of the lead-free ceramic cantilever beam sample provided in Examples 1-6. Finally, the laser beam of the laser vibrometer is tested by the Doppler effect to obtain the displacement size of the photostrictive ceramic cantilever beam sample.
[0087] Figure 3 4 is a test result diagram of the photostrictive lead-free ceramic material provided in Example 4 of the present invention generating photoinduced strain under light driving conditions, such as Figure 3 As shown, the displacement of the entire ceramic cantilever beam was measured by a laser vibrometer, and then the displacement value at the free end of the cantilever beam was selected and recorded as the maximum light-induced displacement. The maximum light-induced displacement value of Example 4 was 202.10 nanometers.
[0088] According to the displacement value, the strain calculation formula of the ceramic cantilever beam is:
[0089] ε0=ΔL / L=h / 2R=h×δ / (L 2 +δ 2 )
[0090] Wherein, h is the thickness of the cantilever beam sample, δ is the maximum displacement value of the cantilever beam sample, L is the length of the cantilever beam sample, and R is the bending radius of the cantilever beam.
[0091] The calculated photoinduced strain value is 1.12×10 -5 , according to its resonant frequency of 9.1kHz, combined with |dε / dt| max =2πfε0, the photoinduced strain rate is 6.40×10 -1 .
[0092] Figure 41 is a comparison chart of the photoinduced strain and photoinduced strain rate of the lead-free ceramic materials of the photostrictive response of Examples 1-6 of the present invention as a function of the composition. Figure 4 As shown, the lead-free ceramic cantilever beam prepared with the components of x=0.02, y=0.03, z=0.06 corresponding to Example 4 can obtain the largest photoinduced deformation and the highest photoinduced strain rate.
[0093] Figure 5 The electric domain structure diagrams of the lead-free ceramic materials with photostrictive response of Examples 1, 3, 4, and 6 of the present invention taken by piezoelectric force microscope (the upper row is the phase diagram, and the lower row is the amplitude diagram); Figure 5 As shown, with the increase of doping content, the size of the ferroelectric domain structure inside the example sample gradually decreases, evolving from a micron-sized ferroelectric domain to a nano-sized ferroelectric domain structure.
[0094] Figure 6 is a deformation amount diagram corresponding to the micro-domain reversal of the photostrictive responsive lead-free ceramic material of Examples 1, 3, 4, and 6 of the present invention, Figure 7 is a phase diagram corresponding to the micro-domain reversal of the lead-free ceramic material of the photostrictive response of embodiments 1, 3, 4, and 6 of the present invention; Figure 6-7 As shown, with the increase of doping content, the micro-region piezoelectric response of the example samples will be significantly different, among which the lead-free ceramic prepared with the components of x=0.02, y=0.03, z=0.06 corresponding to Example 4 can show the most excellent local piezoelectric response under a small voltage excitation signal.
[0095] Figure 8 4 is a test result diagram of the ceramic cantilever beam used to generate ultrasonic waves in Example 4 of the present invention. Figure 8 As shown, continuous modulated light (modulation frequency is the resonant frequency of the cantilever beam) is used to irradiate the KNN-0.02Tb cantilever. The generated oscillating strain can effectively excite ultrasonic waves, which propagate in the aluminum plate and are finally detected by the laser scanning vibrometer. The scanning results show that ultrasonic waves can be effectively coupled into the aluminum plate, showing periodicity with a wavelength of 18.1 mm. The obtained ultrasonic signal is then analyzed using a damped sine wave function to analyze its attenuation propagation in the aluminum plate. The ultrasonic frequency detected on the aluminum plate is consistent with the modulation frequency of the incident light, which is 50.3kHz.
[0096] The photostrictive properties of the lead-free ceramic materials with photostrictive response in Examples 1-6 of the present invention are shown in Table 1.
[0097] Table 1 Photostrictive performance data of lead-free ceramic materials with photostrictive response in Examples 1-6
[0098]
[0099] As shown in Table 1, after doping with Tb, Bi, and Li elements, the photoinduced strain of the lead-free ceramic material with the best photostrictive performance can reach 1.12×10 -5 , the corresponding photoinduced strain rate can reach 6.40×10 -1 , which is much higher than the photoinduced strain of undoped photostrictive ceramic materials of 6.11×10 -9 and the photoinduced strain rate is 3.49×10 -4 .
[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A lead-free ceramic with fast and efficient photostrictive response, characterized in that: Including K 0.5 Na 0.5 NbO3-based ceramics and doping elements, the doping elements are Tb, Bi and Li, and the chemical formula of lead-free ceramics is: <h2 style=";text-align:left;direction:ltr">[(K<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> Na<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> 1-z <h2 style=";text-align:left;direction:ltr"> Li<h2 style=";text-align:left;direction:ltr"> z <h2 style=";text-align:left;direction:ltr"> ](Nb<h2 style=";text-align:left;direction:ltr"> 1-y <h2 style=";text-align:left;direction:ltr"> Bi<h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> )O3-xTb; Wherein, x, y, z represent the doping amount, x = 0.01, 0.02, 0.03, 0.04; y = 0.03; z = 0.06; The lead-free ceramic is used to generate ultrasonic waves.
2. A method for preparing a lead-free ceramic having a fast and efficient photostrictive response as claimed in claim 1, characterized in that: The following steps are involved: S101, selecting potassium carbonate, sodium carbonate, niobium pentoxide, bismuth oxide, lithium carbonate, and terbium oxide as raw materials according to molar percentage, and using anhydrous ethanol as a ball milling medium, rolling ball milling to obtain a uniform powder; S102, drying the powder obtained in S101 to obtain a uniformly mixed powder; S103, pre-calcining the powder obtained in S102 at 700-900° C. for 2-9 hours to obtain dry powder; S104, adding a polyvinyl alcohol aqueous solution to the dry powder obtained in S103, and sequentially performing granulation, pressing and debinding to obtain a ceramic body; S105, sintering the ceramic body obtained in S104 at 1000-1200° C. for 5-20 hours to obtain a photostrictive lead-free ceramic body; S106. Cut the lead-free ceramic body obtained in S105 into a ceramic cantilever beam with a length×width×height of 3.00 mm×0.25 mm×0.50 mm using a precision cutting machine.
3. The method for preparing a lead-free ceramic having a fast and efficient photostrictive response according to claim 2, characterized in that: The ball mill jar used in S101 is a nylon jar, and the grinding balls used are zirconium balls.
4. The method for preparing a lead-free ceramic having a fast and efficient photostrictive response according to claim 2, characterized in that: During the pre-firing in S103, the powder is placed in a corundum crucible, and the corundum crucible is pre-firing at 700 to 900° C. for 2 to 9 hours.
5. The method for preparing a lead-free ceramic having a fast and efficient photostrictive response according to claim 2, characterized in that: The pressing in S104 is as follows: placing the dry powder in a mold having a cavity, and pressing the dry powder into a tablet shape using a hand-operated tablet press or an electric tablet press.
6. The method for preparing a lead-free ceramic having a fast and efficient photostrictive response according to claim 5, characterized in that: The pressure of the electric tablet press is 5-10Mpa.
7. The method for preparing a lead-free ceramic having a fast and efficient photostrictive response according to claim 2, characterized in that: The mass percentage of the polyvinyl alcohol aqueous solution in S104 is 3wt% to 8wt%.
Citation Information
Patent Citations
Method for preparing potassium-sodium niobate textured ceramic and potassium-sodium niobate single crystal
CN101913868A
Preparation method of holmium-doped potassium sodium niobate-based transparent ceramic
CN108840677A
Method for preparing holmium / lithium / bismuth modified potassium-sodium niobate luminescent transparent ceramic based on tape casting
CN110372380A